The monothiol glutaredoxin Grx4 influences thermotolerance, cell wall integrity, and Mpk1 signaling in Cryptococcus neoformans. Issue 11 (7th September 2021) - Hu, Guanggan; Horianopoulos, Linda; Sánchez-León, Eddy; Caza, Mélissa; Jung, Wonhee; Kronstad, James W
Abstract: Monothiol glutaredoxins are important regulators of iron homeostasis that play conserved roles in the sensing and trafficking of iron-sulfur clusters. We previously characterized the role of the monothiol glutaredoxin Grx4 in iron homeostasis, the interaction with the iron regulator Cir1, and virulence in Cryptococcus neoformans . This important fungal pathogen causes cryptococcal meningoencephalitis in immunocompromised individuals worldwide. Here, we demonstrate that Grx4 is required for proliferation at elevated temperatures (both 37°C and 39°C) and under stress conditions. In particular, the grx4Δ mutant was hypersensitive to SDS, calcofluor white (CFW), and caffeine, suggesting that Grx4 is required for membrane and cell wall integrity (CWI). In this context, we found that Grx4 regulated the phosphorylation of the Mpk1 mitogen-activated protein kinase (MAPK) of the CWI pathway in cells grown at elevated temperature or upon treatment with CFW, caffeine, or SDS. The grx4Δ mutant also displayed increased sensitivity to FK506 and cyclosporin A, two inhibitors of the calcineurin pathway, indicating that Grx4 may influence growth at higher temperatures in parallel with calcineurin signaling. Upon thermal stress or calcium treatment, loss of Grx4 also caused partial mis-localization of Crz1, the transcription factor that is a calcineurin substrate. The phenotypes of the grx4Δ, crz1Δ, and cna1Δ (calcineurin) mutants suggest shared contributions to the regulation of temperature, cell wall, and other stresses. In summary, we show that Grx4 is also a key regulator of the responses to a variety of stress conditions in addition to its roles in iron homeostasis in C. neoformans.